2020
DOI: 10.20473/jn.v15i1.16597
|View full text |Cite
|
Sign up to set email alerts
|

Modern and Classic Wound Dressing Comparison in Wound Healing, Comfort and Cost

Abstract:  Introduction: Wound care has also developed rapidly after the dissemination of the concept of TIME (Tissue, Infection, Moisture, and Wound Edge) in modern dressing (MD). The aim of this study was to compare modern dressings (MDs) and classic dressings (CDs) in terms of patient comfort, cost effectiveness and wound healing.Methods: A prospective study design with total of 25 participants. The sampling technique used was consecutive sampling. Patient comfort was assessed through the frequency of wound c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
0
14
0
4
Order By: Relevance
“…Conversely, modern wound dressings (foam, film, hydrocolloid, alginate, and foam dressings) can be changed every few days, shortening the time nurses must spend on each patient. Previous studies also showed that the use of modern wound dressings can significantly reduce pain and shorten healing time [ [41] , [42] , [43] , [44] ]. Although modern wound dressing has been used extensively since the 1980s in U.S. and European hospitals [ 45 ], it was only introduced to Indonesian hospitals in the early 2000s, and remains rare.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, modern wound dressings (foam, film, hydrocolloid, alginate, and foam dressings) can be changed every few days, shortening the time nurses must spend on each patient. Previous studies also showed that the use of modern wound dressings can significantly reduce pain and shorten healing time [ [41] , [42] , [43] , [44] ]. Although modern wound dressing has been used extensively since the 1980s in U.S. and European hospitals [ 45 ], it was only introduced to Indonesian hospitals in the early 2000s, and remains rare.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalensi kejadian luka secara global meningkat setiap tahunnya, diperkirakan dalam populasi 1 juta orang, terdapat sekitar 3500 orang hidup dengan luka, 525 di antaranya mengalami luka selama lebih dari 1 tahun, hal ini juga mengakibatkan meningkatnya biaya pengobatan yang diperkirakan menghabiskan hampir 3% dari total biaya sistem kesehatan (Lindholm & Searle, 2016). Angka kejadian luka di Indonesia pun cukup tinggi bersama dengan peningkatan jumlah kecelakaan lalu lintas dalam beberapa tahun terakhir (Mahyudin et al, 2020).…”
Section: Pendahuluanunclassified
“…Penatalaksanaan luka adalah tindakan perawatan luka yang mencakup semua elemen termasuk kontrol komorbid dan komplikasi yang dapat terjadi akibat luka tersebut. Rangkaian kegiatan tersebut antara lain membersihkan luka dan mengganti balutan (Mahyudin et al, 2020). Perawatan luka konvensional yang sering dilakukan dengan menggunakan tulle dan kain kasa membutuhkan waktu penyembuhan yang lama, terutama untuk luka kronis dengan komplikasi tertentu.…”
Section: Pendahuluanunclassified
“…Lama perawatan dan kunjungan yang dilakukan oleh tenaga medis yang perlu lebih sering akan berdampak pada biaya perawatan. Selain itu, dari segi kenyamanan, pasien yang dirawat dengan perban konvensional seringkali mengeluhkan nyeri saat dibalut karena lukanya cenderung menempel dengan balutan (Mahyudin et al, 2020).…”
Section: Pendahuluanunclassified